الإطار القانوني لاندماج الشركات التجارية: دراسة مقارنة بين النظام السعودي والقانون المصري - الغامدي، حمدان بن درويش (جامعة الأزهر - كلية الشريعة والقانون بدمنهور, 2024)
يتناول هذا البحث موضوع اندماج الشركات التجارية في النظام السعودي من منظور مقارن، مع التركيز على الأهمية المتزايدة لهذا الموضوع في ظل التطورات الاقتصادية والتكنولوجية الراهنة. وتبرز الدراسة الحاجة الملحة للشركات، خاصة الصغيرة والمتوسطة، إلى تبني استراتيجيات الاندماج كوسيلة لتعزيز قدراتها التنافسية والحفاظ على استمراريتها في سوق يهيمن عليه اللاعبون الكبار والتكنولوجيا المتقدمة. يستعرض البحث تعريف الاندماج وأنواعه، سواء كان أفقيا أو رأسيا، ويناقش الإجراءات القانونية والاقتصادية اللازمة لتحقيق اندماج ناجح. كما يلقي الضوء على التحديات التي تواجه الشركات خلال وبعد الاندماج، مع تقديم توصيات لمعالجة هذه التحديات. تأتي أهمية البحث من الدور الفعال الذي يمكن أن يلعبه الاندماج في دعم الاقتصاد الوطني، من خلال تحسين الكفاءة الإنتاجية وتعزيز الابتكار. يؤكد الباحث على أن التشريعات السعودية الحديثة قد منحت اهتمامًا كبيرًا لهذه العملية، بما في ذلك تحديث الأحكام القانونية لتسهيل عمليات الاندماج. من خلال تحليل مقارن بين النظام السعودي والقانون المصري بشأن اندماج الشركات، يسعى البحث إلى تسليط الضوء على أفضل الممارسات والدروس المستفادة التي يمكن تطبيقها لتعزيز فعالية عمليات الاندماج في السعودية. يختتم البحث بسلسلة من التوصيات الموجهة للمشرعين والشركات على حد سواء، بهدف تحسين الإطار التنظيمي والعملي لاندماج الشركات، وبالتالي دعم النمو الاقتصادي والتنمية المستدامة في المملكة العربية السعودية. This research addresses the issue of the merger of commercial companies in the Saudi regulation from a comparative perspective, focusing on the increasing importance of this topic in light of current economic and technological developments. The study highlights the urgent need for companies, especially small and medium-sized ones, to adopt merger strategies as a means to enhance their competitive capabilities and maintain their continuity in a market dominated by large players and advanced technology. The research tackles the definition of merger and its types, whether horizontal or vertical ones, and discusses the legal and economic procedures necessary to achieve successful merger. It also sheds light on the challenges facing companies during and after the merger, while providing recommendations to address these challenges. The importance of the research springs from the effective role that merger can play in supporting the national economy through improving production efficiency and promoting innovation. The researcher emphasizes that modern Saudi regulations have paid great attention to this process, including updating legal provisions to facilitate mergers. Through comparative analysis between Saudi regulation and the Egyptian law concerning the merger of companies, the research seeks to highlight the best practices and lessons that can be applied to promote the effectiveness of merger in Saudi Arabia. The research concludes with a series of recommendations directed at legislators and companies alike, with the aim of improving the regulatory and practical framework for merger of companies. Thus, economic growth and sustainable development can be enhanced in the Kingdom of Saudi Arabia.
يحتوي على العنوان الآتي: اندماج الشركات التجارية في النظام السعودي: دراسة مقارنة
Keywords: اندماج الشركات -- الشركات التجارية -- الاقتصاد الوطني -- المحاكم التجارية -- القانون السعودي -- القانون المصري